Preliminary Effectiveness of Project ImPACT: A Parent-Mediated Intervention for Children with Autism Spectrum Disorder Delivered in a Community Program - Stadnick, Nicole A. (J Autism Dev Disord, 2015)
This is a pilot study of the effectiveness of Project ImPACT, a parent-mediated intervention for ASD delivered in a community program. The primary aim was to compare child and parent outcomes between the intervention group and a community comparison for 30 young children with ASD at baseline and 12 weeks. The secondary aim was to identify parent factors associated with changes in child outcomes. Results indicated significant improvement in child communication skills and a strong trend for parent intervention adherence for the intervention group from baseline to 12 weeks. Higher baseline parenting stress was negatively related to child social gains from baseline to 12 weeks. Findings provide further support for delivering parent-mediated interventions in community settings to children with ASD.